Penyebab Utama Terjadinya Tindak Pidana Pelecehan Seksual Inses (Hubungan Sedarah) - Yulia Hesti; Rahmi Fitrinoviana Salsabila; Agnestika Agnestika (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
Incestuous abuse is a very serious problem among society, especially among minors. In this research, the main aim was to prevent and understand the main causes of criminal acts of incestuous sexual harassment. So that we can examine in more depth the low level of public awareness and low level of education, the research was conducted using normative juridical methods. So, by socializing PPPA to the community, it can reduce the level of sexual harassment that occurs.